Does distance between aquatic plant assemblages matter in defining similarity between them during high water‐level periods? - Paiva, José de Ribamar A; Matias, Lígia Q; Martins, Fernando R; Becker, Helena (Lakes & Reservoirs : Science, Policy and Management for Sustainable Use, 2014)
Aquatic environments are subject to natural water‐level fluctuations. These fluctuations, in turn, are responsible for causing changes in biota in the aquatic environment, particularly those that colonize floodplains. The flood pulse concept predicts that water‐level fluctuations are responsible for the formation of mosaics in biota at a small scale. During high water‐level periods, however, there is evidence that the similarity among biological assemblages increases. Within this theoretical context, the present study focuses on determining whether or not the spatial distance between assemblages is a relevant factor for the similarity among them during high water‐level periods and, if not, what environmental variables are associated with them? Accordingly, the present study evaluated the association between aquatic plant assemblages and some environmental variables, with emphasis on the spatial distance among assemblages. The study results indicated no association between the similarity of the assemblages and the spatial distances between them. The environmental variables most associated with the assemblages were the total phosphorus and nitrate concentrations. It was concluded that, during high water‐level periods, the spatial distance between aquatic plant assemblages was not a relevant factor for greater similarity among them. Rather, the total phosphorus and nitrate concentrations were the environmental factors most associated with the assemblages.